Photocatalytic Mechanism and Performance Improvement of Ti3C2 for the Treatment of Tetracycline Antibiotics - Liu, Zeng; Wang , Hao (Scientific Journal of Technology, 2025)
Compared to traditional wastewater treatment processes, advanced oxidation processes (AOP) can more effectively and environmentally friendly remove harmful substances from wastewater. Among these, photocatalytic oxidation (PCO) has garnered significant attention due to its ability to utilize solar energy for pollutant removal. With the rapid development of industry and medicine, tetracycline (TC), an antibiotic detectable at various levels of the aquatic and terrestrial ecosystems’ food chains, poses long-term environmental pollution and biological toxicity risks due to its persistent residues. Conventional treatment processes are ineffective in addressing this issue. Therefore, in recent years, research related to PCO in wastewater treatment has flourished, and numerous researchers have reviewed its recent progress.However the main challenges and future directions of PCO are still not fully analyzed. In this paper, we first review the catalytic mechanism and various control factors of PCO. Then, we discuss the current development status of the main photocatalyst-Ti3C2 and summarize their commonly used evaluation criteria and systems. Finally, on this basis, we analyze the main challenges faced by Ti3C2 in theoretical studies and practical applications and propose the optimization and improvement of Ti3C2 to meet the feasibility in industrial applications. We believe that the research in this paper will provide important guidance and reference for enhancing Ti3C2 as a photocatalyst in the field of wastewater treatment.